Analysis Implementing Obstacles of State Elementary School 2 Kebumen in the 2013 Curriculum - Hanif Imadudin; Astika Krisnawati; Syifa' Lana; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2019)
This study was intended to see obstacles in implementing the 2013 curriculum by elementary school teacher 2 Kebumen. This study uses qualitative descriptive assessment methods. The subject of this study is 6 elementary school teachers 2 Kebumen made up of 6 class teachers. Data collection using angers and interviews. Studies show that the obstacles that elementary school teacher 2 Kebumen experienced in implementation of the 2013 that is in the plannin phase, implement phase, and evaluation phase. Obstacles include learning preparation, slection and media lerning making, insight teacher, cross-loading of lessons in thematic learning, and It literacy.